2018
DOI: 10.3765/plsa.v3i1.4351
|View full text |Cite
|
Sign up to set email alerts
|

Suffix interference in Russian

Abstract: Abstract. The phenomenon of "suffix interference" has been used as evidence for a distinction between inflectional and derivational processes (e.g. Pinker & Prince, 1988;Pinker, 1999;Pinker & Ullman, 2002). Yet much of the work on affix priming exists in English, a morphologically poor language, and suffix interference appears inconsistently in cross-linguistic data. The greater reliance on morphological complexity in Russian, and its use of an infinitival suffix and aspectual affixes that may bridge the disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
1
Order By: Relevance
“…In experiment 3 (prefixedprefixed), we found that prefixed words reliably primed other morphologically related prefixed words. In experiment 4 (suffixed-suffixed), the findings also suggest that morphologically related suffixed items prime each other readily in Bengali, contrary to the lack of priming found for suffixed words in Marslen-Wilson et al 1994, Feldman & Soltano 1999, Gonnerman & Andersen 2000, Reid & Marslen-Wilson 2000, Feldman & Larabee 2001, and Comstock 2018 In comparing the degree of priming between prefixed-prefixed and suffixed-suffixed configurations, however, we found a substantial difference. While the prefixedprefixed configuration exhibited a priming effect size of 84 ms, the suffixed word pairs exhibited a priming effect size of only 21 ms.…”
Section: Rtcontrasting
confidence: 69%
“…In experiment 3 (prefixedprefixed), we found that prefixed words reliably primed other morphologically related prefixed words. In experiment 4 (suffixed-suffixed), the findings also suggest that morphologically related suffixed items prime each other readily in Bengali, contrary to the lack of priming found for suffixed words in Marslen-Wilson et al 1994, Feldman & Soltano 1999, Gonnerman & Andersen 2000, Reid & Marslen-Wilson 2000, Feldman & Larabee 2001, and Comstock 2018 In comparing the degree of priming between prefixed-prefixed and suffixed-suffixed configurations, however, we found a substantial difference. While the prefixedprefixed configuration exhibited a priming effect size of 84 ms, the suffixed word pairs exhibited a priming effect size of only 21 ms.…”
Section: Rtcontrasting
confidence: 69%